결혼이주여성을 위한 한국 식문화 교육용 교재 개발 - 이정숙(Jeong-Sook Lee) (Korean journal of community nutrition, 2016)
Objectives: The purpose of the study was to develop a textbook of the integrated education of Korean food culture and language for married female immigrants. Methods: An analysis was conducted with the textbooks and researches for married female immigrants, and dietary life related contents were extracted. The contents were organized by activity oriented approach which is acquired the culture. The evaluation was conducted through depth interview with 6 married female immigrants through an analysis of the qualitative materials. Results: The text book comprised of 30 Korean food recipes with the target expressions and vocabularies. It also included Korean basic table setting, Korean table manner, main dishes and side dishes, basic cutting, seasoning and garnish, measure of the ingredients, symbolic food, regional food culture, choice of food ingredients, shopping, bargaining, taste expression, color expression, all sorts of spices, Korean traditional festival food, and seasonal customs and food. For intensifying communication, activity which is close to real life was added. Through cooking, married female immigrants expose words and sentence patterns and that allows to evaluate their level of understanding. We observed that the developed textbook is suited for married female immigrants' needs and cognitive level. The text book included a comparative study between Korean culture and their country's culture, which could provide the motive for accepting each other's cultures. The study showed how to develop a textbook that integrates Korean language education and Korean food culture and how to apply the textbook in real life. Conclusions: The correct understanding about Korean food culture could lead to improvements communication ability. Useful information which relates to Korean food, recipes, and food culture could increase daily life satisfaction. Conducting both cultural education and language education could increase the participation of married female immigrants in learning activities. Therefore this study could help these females to adapt Korean society and manage family dietary life effectively.